Kendali Kecepatan Switched Reluctance Motor Berbasis FPGA - Wibisono, Arifin; Riyadi, Slamet; Sulaiman, Sulaiman (PROtek : Jurnal Ilmiah Teknik Elektro, 2022)
Abstract-- Renewable drive technology is developing in the current era, one of which is electric transportation. The Switched Reluctance Motor (SRM) was chosen for the transportation development because it has many advantages, including not using permanent magnets and simple construction in the form of an iron core in the rotor and stator windings. SRM works based on the reluctance phenomenon, namely, if the stator is energized, the stator will attract the nearby rotor, this is based on the tendency of the rotor poles to align with the stator excitation poles. SRM requires high speed switching control to operate and requires correct rotor position to operate. Maximum switching and good accuracy can use Field-Programmable Gate Array (FPGA) and rotary encoder as input for rotor position information. To use SRM in electric transport, it is necessary to adjust the speed with ease and precision. With the Pulse Width Modulation (PWM) technique, the size of the excitation depends on the size of the current, the size of the current is determined by the input voltage to the SRM. In this control, the PWM width can be changed by setting the carrier set and modulation set in the FPGA program. In this study, it is proposed to control the SRM speed by adjusting the PWM of the rotary encoder to produce the desired RPM. To support the achievement of this research, hardware testing was carried out in the laboratory.Keywords-- Duty cycle, FPGA, PWM, Reluctance, Switched Reluctance Motor.